PEMBERDAYAAN TEMPAT PENITIPAN ANAK (TPA) DALAM PENGELOLAAN PENYAKIT MENULAR SERTA SKRINING TUMBUH KEMBANG ANAK DI TPA PURI RARE KOTA DENPASAR - Ni Putu Diah Witari; Anny Eka Pratiwi; Ni Komang Trisna Sumadewi (JURNAL SEWAKA BHAKTI, 2021)
Day care centers are currently experiencing significant developments with the many needs of the community and demands of parents to work. So that many parents leave their children in child care centers (TPA). Puri Rare Day Care is one of the TPAs in the city of Denpasar. Several toddlers and children were sent there. Toddlers and children are vulnerable to infection in TPA, so the aim of this Service is to provide knowledge about infectious diseases and their prevention and training to use self-protection tools and screening for child development. Mita's participation reached 100% and there was an increase in partners' knowledge about child infectious diseases and how to prevent them as well as child growth and development from 53.33 to 86.67% and monitoring and evaluation every 2 weeks to see the ability of partners in screening growth and development and prevention of infection. After carrying out PKM activities, it can be concluded that there is an increase in partners' knowledge about infectious diseases and their prevention and how to screen children's growth and development.